Preparation method of decorative base paper
By preparing composite fillers by combining materials such as lene, zirconia, potassium titanate and titanium dioxide, and combining them with modifiers such as polysiloxane, and preparing decorative base paper in wood slurry, the problem of existing decorative base paper being easily broken when improving the covering performance and tensile strength is solved, and high covering, tensile strength and whiteness are improved.
Patent Information
- Application Number
- CN202510206027.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-02-25
AI Technical Summary
When existing decorative base paper improves the covering performance and tensile strength, it is easy to cause the paper to break and tear, and it is difficult to meet the requirements of high whiteness and printing adaptability at the same time.
Composite fillers are prepared by ball milling materials such as elarite, zirconia, potassium titanate and titanium dioxide, and combined with modifiers such as polysiloxane to form modified composite fillers. They are added to a mixed slurry of bleached sulfate eucalyptus pulp and spruce pulp. After internet crissing, wet paper sheet molding and pressing and drying, decorative base paper with excellent covering properties, tensile strength and whiteness are prepared.
The high hiding performance, tensile strength and whiteness of decorative base paper are achieved, which avoids cracking and tearing of paper during processing, and extends the service life of paper.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of papermaking, and specifically relates to a method for preparing decorative base paper. Background Art
[0002] Decorative base paper is one of the special products of the papermaking industry, mainly used for processing and manufacturing various home furnishing boards, laminate flooring, fireproof boards and other decorative materials. Excellent decorative base paper should have good hiding and absorption properties, and for printing decorative base paper, it should also have good printing adaptability. There are three differences between decorative base paper and ordinary paper: extremely high filler content; no internal sizing agent; no surface sizing. At the same time, in order to meet the needs of post-processing printing, there are strict requirements on technical indicators such as quantitative, tensile strength, wet strength, smoothness and uniformity.
[0003] The performance of high-quality decorative base paper requires systematic design of raw materials and production processes to achieve. For example, when the decorative base paper is covered on the surface of building materials, its hiding power is extremely high. The current common way to improve the hiding power of decorative base paper is to increase the amount of fillers such as titanium dioxide to increase the opacity of the paper. However, when the amount of fillers such as titanium dioxide is too high, the tensile strength of the paper will be too low, which will cause the staff to break and tear the paper due to the necessary flipping of the paper when impregnating the decorative base paper with paint and decorative patterns.
[0004] Therefore, it is necessary to explore a new method for preparing decorative base paper. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing decorative base paper. The decorative base paper prepared by the method has good hiding performance, tensile strength and whiteness.
[0006] The method for preparing the decorative base paper of the present invention comprises the following steps:
[0007] (1) Pyrophyllite, zirconium oxide, potassium titanate, sodium hexametaphosphate and deionized water are uniformly mixed and ball-milled to prepare a suspension, titanium dioxide is added to the suspension and ball-milled for a second time, and then filtered and dried to prepare a composite filler;
[0008] (2) dissolving the composite filler prepared in step (1) in water, then adding acetic acid to adjust the pH value of the system to 4, adding polysiloxane after high-speed stirring to react, filtering, washing, and drying after the reaction is completed to prepare a modified composite filler;
[0009] (3) pulping and beating bleached eucalyptus sulfate pulp and bleached spruce sulfate pulp to obtain bleached eucalyptus sulfate pulp slurry and bleached spruce sulfate pulp slurry, respectively, and then mixing the bleached eucalyptus sulfate pulp slurry and the bleached spruce sulfate pulp slurry to prepare a mixed slurry;
[0010] (4) Adding the modified composite filler, dialdehyde starch, polyethyleneimine and sodium tripolyphosphate prepared in step (2) to the mixed slurry prepared in step (3), stirring to make the mixture uniformly mixed to prepare a slurry, and then sequentially subjecting the obtained slurry to screen papermaking, wet paper sheet forming, and pressing and drying to prepare a decorative base paper.
[0011] in:
[0012] In step (1), the mass ratio of pyrophyllite, zirconium oxide and potassium titanate is 1:0.2-0.3:0.5-0.7.
[0013] In step (1), the mass ratio of the mixture of pyrophyllite, zirconium oxide and potassium titanate to sodium hexametaphosphate is 1:0.002.
[0014] In step (1), the mass ratio of the mixture of pyrophyllite, zirconium oxide and potassium titanate to deionized water is 1:1.7.
[0015] In step (1), the first ball milling speed is 1000 r / min, the first ball milling time is 110-115 min, the second ball milling speed is 1100 r / min, and the second ball milling time is 45-50 min.
[0016] In step (1), the mass ratio of the mixture of titanium dioxide and pyrophyllite, zirconium oxide and potassium titanate is 3-4:6-7.
[0017] In step (1), alumina grinding beads are used as grinding media in both the first ball milling and the second ball milling, and the medium ratio is 1:10.
[0018] In step (1), the drying temperature is 103-105° C. and the drying time is 4-4.5 h.
[0019] In step (2), the mass ratio of the composite filler to water is 1:30.
[0020] In step (2), the mass of the polysiloxane accounts for 0.2%-0.3% of the mass of the composite filler.
[0021] In step (2), the rotation speed of high-speed stirring is 800 r / min, the time of high-speed stirring is 55-60 min, the reaction temperature is 68-70° C., and the reaction time is 4.8 h.
[0022] In step (2), anhydrous ethanol is used for washing 3-4 times, the drying temperature is 103-105° C., and the drying time is 5 hours.
[0023] The manufacturers of the bleached eucalyptus kraft pulp and the bleached spruce kraft pulp in step (3) are both Guangxi Guangye Guitang Sugar Industry Group Co., Ltd.
[0024] In step (3), the mass ratio of bleached eucalyptus kraft pulp to bleached spruce kraft pulp is 4:6.
[0025] In step (3), the beating degree of the bleached eucalyptus sulfate pulp is 35°SR, and the mass concentration of the bleached eucalyptus sulfate pulp slurry is 5.5%; the beating degree of the bleached spruce sulfate pulp is 33°SR, and the mass concentration of the bleached spruce sulfate pulp slurry is 4.0%.
[0026] In step (4), the mass of the modified composite filler accounts for 16.5-17.5% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp, the mass of the dialdehyde starch accounts for 1.1-1.3% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp, the mass of the polyethyleneimine accounts for 0.7-0.9% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp, and the mass of the sodium tripolyphosphate accounts for 0.5% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp.
[0027] In step (4), the stirring speed is 1200 r / min and the stirring time is 40-45 min.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The method for preparing decorative base paper of the present invention comprises adding a modified composite filler to a mixed pulp consisting of bleached kraft eucalyptus pulp and bleached kraft spruce pulp, and simultaneously adding dialdehyde starch, polyethyleneimine and sodium tripolyphosphate, so that the prepared decorative base paper has excellent whiteness, opacity and tensile strength.
[0030] (2) The method for preparing decorative base paper of the present invention comprises the following steps: in step (1), titanium dioxide is coated on the surface of a mixture of pyrophyllite, zirconium oxide and potassium titanate to prepare a composite filler, and Si-O-Ti chemical bonds are formed after coating, thereby improving the whiteness and mechanical properties of the composite filler. In step (2), polysiloxane is added for further modification to make it hydrophobic, so that the formed modified composite filler has good bonding strength with pulp fibers, and yellowing or powdering does not occur during the papermaking process, thereby extending the service life of the paper and further improving the comprehensive properties of the decorative base paper.
[0031] (3) The method for preparing decorative base paper of the present invention comprises the following steps: in step (1), titanium dioxide is coated on the surface of a mixture of pyrophyllite, zirconium oxide and potassium titanate to prepare a composite filler, thereby improving the whiteness and mechanical properties of the filler. Pyrophyllite itself is a layered aluminum silicate mineral, which has high whiteness and hiding power, and has a dense structure and good chemical stability. Replacing part of titanium dioxide with pyrophyllite can improve the whiteness and hiding power of the composite filler. Zirconium dioxide is compounded, and zirconium dioxide can improve the reflection and scattering ability of the composite filler to light, and zirconium dioxide has good hardness and wear resistance. The filler prepared in this way can form a stable supporting structure in the paper, thereby improving the tensile strength of the paper. The addition of potassium titanate can improve the retention rate of the filler, reduce the loss of the filler during the papermaking process, enhance the bonding force between fibers, and improve the tensile strength of the paper.
[0032] (4) The method for preparing the decorative base paper of the present invention comprises selecting bleached kraft eucalyptus pulp and bleached kraft spruce pulp for compound use, wherein the bleached kraft spruce pulp has long fibers and high strength and toughness, while the bleached kraft eucalyptus pulp has short fibers and good softness and smoothness. The combination of the two ensures the tensile strength and surface properties of the prepared decorative base paper.
[0033] (5) In the method for preparing decorative base paper of the present invention, dialdehyde starch and polyethyleneimine work synergistically to further improve the mechanical properties of the decorative base paper, wherein the highly active aldehyde groups in dialdehyde starch cross-link with the hydroxyl groups of pulp fibers to form a stable acetal structure, while polyethyleneimine enhances the bonding force between fibers through a bridging effect. The two work synergistically to improve the dispersibility of the modified composite filler while allowing the decorative base paper to form a more stable network structure, thereby improving the tensile strength of the paper. DETAILED DESCRIPTION
[0034] The present invention is further described below with reference to the embodiments.
[0035] Example 1
[0036] The method for preparing the decorative base paper described in Example 1 comprises the following steps:
[0037] (1) Pyrophyllite, zirconium oxide, potassium titanate, sodium hexametaphosphate and deionized water are uniformly mixed and ball-milled to prepare a suspension, titanium dioxide is added to the suspension and ball-milled for a second time, and then filtered and dried to prepare a composite filler;
[0038] (2) dissolving the composite filler prepared in step (1) in water, then adding acetic acid to adjust the pH value of the system to 4, adding polysiloxane after high-speed stirring to react, filtering, washing, and drying after the reaction is completed to prepare a modified composite filler;
[0039] (3) pulping and beating bleached eucalyptus sulfate pulp and bleached spruce sulfate pulp to obtain bleached eucalyptus sulfate pulp slurry and bleached spruce sulfate pulp slurry, respectively, and then mixing the bleached eucalyptus sulfate pulp slurry and the bleached spruce sulfate pulp slurry to prepare a mixed slurry;
[0040] (4) Adding the modified composite filler, dialdehyde starch, polyethyleneimine and sodium tripolyphosphate prepared in step (2) to the mixed slurry prepared in step (3), stirring to make the mixture uniformly mixed to prepare a slurry, and then sequentially subjecting the obtained slurry to screen papermaking, wet paper sheet forming, and pressing and drying to prepare a decorative base paper.
[0041] in:
[0042] In step (1), the mass ratio of pyrophyllite, zirconium oxide and potassium titanate is 1:0.25:0.6.
[0043] In step (1), the mass ratio of the mixture of pyrophyllite, zirconium oxide and potassium titanate to sodium hexametaphosphate is 1:0.002.
[0044] In step (1), the mass ratio of the mixture of pyrophyllite, zirconium oxide and potassium titanate to deionized water is 1:1.7.
[0045] In step (1), the first ball milling speed is 1000 r / min, the first ball milling time is 113 min, the second ball milling speed is 1100 r / min, and the second ball milling time is 47 min.
[0046] In step (1), the mass ratio of the mixture of titanium dioxide and pyrophyllite, zirconium oxide and potassium titanate is 3.5:6.5.
[0047] In step (1), alumina grinding beads are used as grinding media in both the first ball milling and the second ball milling, and the medium ratio is 1:10.
[0048] In step (1), the drying temperature is 104° C. and the drying time is 4.3 h.
[0049] In step (2), the mass ratio of the composite filler to water is 1:30.
[0050] The mass of the polysiloxane in step (2) accounts for 0.25% of the mass of the composite filler.
[0051] In step (2), the rotation speed of high-speed stirring is 800 r / min, the time of high-speed stirring is 58 min, the reaction temperature is 69° C., and the reaction time is 4.8 h.
[0052] In step (2), anhydrous ethanol is used for washing 4 times, the drying temperature is 104° C., and the drying time is 5 h.
[0053] The manufacturers of the bleached eucalyptus kraft pulp and the bleached spruce kraft pulp in step (3) are both Guangxi Guangye Guitang Sugar Industry Group Co., Ltd.
[0054] In step (3), the mass ratio of bleached eucalyptus kraft pulp to bleached spruce kraft pulp is 4:6.
[0055] In step (3), the beating degree of the bleached eucalyptus sulfate pulp is 35°SR, and the mass concentration of the bleached eucalyptus sulfate pulp slurry is 5.5%; the beating degree of the bleached spruce sulfate pulp is 33°SR, and the mass concentration of the bleached spruce sulfate pulp slurry is 4.0%.
[0056] In step (4), the mass of the modified composite filler accounts for 17% of the total mass of the bleached eucalyptus sulfate pulp and the bleached spruce sulfate pulp, the mass of the dialdehyde starch accounts for 1.2% of the total mass of the bleached eucalyptus sulfate pulp and the bleached spruce sulfate pulp, the mass of the polyethyleneimine accounts for 0.8% of the total mass of the bleached eucalyptus sulfate pulp and the bleached spruce sulfate pulp, and the mass of the sodium tripolyphosphate accounts for 0.5% of the total mass of the bleached eucalyptus sulfate pulp and the bleached spruce sulfate pulp.
[0057] In step (4), the stirring speed is 1200 r / min and the stirring time is 43 min.
[0058] The decorative base paper prepared in Example 1 was tested for its performance, wherein the dry tensile strength was 5.71 kN / m, the whiteness was 94.28%, and the opacity was 98.42%.
[0059] Example 2
[0060] The method for preparing the decorative base paper described in Example 2 comprises the following steps:
[0061] (1) Pyrophyllite, zirconium oxide, potassium titanate, sodium hexametaphosphate and deionized water are uniformly mixed and ball-milled to prepare a suspension, titanium dioxide is added to the suspension and ball-milled for a second time, and then filtered and dried to prepare a composite filler;
[0062] (2) dissolving the composite filler prepared in step (1) in water, then adding acetic acid to adjust the pH value of the system to 4, adding polysiloxane after high-speed stirring to react, filtering, washing, and drying after the reaction is completed to prepare a modified composite filler;
[0063] (3) pulping and beating bleached eucalyptus sulfate pulp and bleached spruce sulfate pulp to obtain bleached eucalyptus sulfate pulp slurry and bleached spruce sulfate pulp slurry, respectively, and then mixing the bleached eucalyptus sulfate pulp slurry and the bleached spruce sulfate pulp slurry to prepare a mixed slurry;
[0064] (4) Adding the modified composite filler, dialdehyde starch, polyethyleneimine and sodium tripolyphosphate prepared in step (2) to the mixed slurry prepared in step (3), stirring to make the mixture uniformly mixed to prepare a slurry, and then sequentially subjecting the obtained slurry to screen papermaking, wet paper sheet forming, and pressing and drying to prepare a decorative base paper.
[0065] in:
[0066] In step (1), the mass ratio of pyrophyllite, zirconium oxide and potassium titanate is 1:0.3:0.5.
[0067] In step (1), the mass ratio of the mixture of pyrophyllite, zirconium oxide and potassium titanate to sodium hexametaphosphate is 1:0.002.
[0068] In step (1), the mass ratio of the mixture of pyrophyllite, zirconium oxide and potassium titanate to deionized water is 1:1.7.
[0069] In step (1), the first ball milling speed is 1000 r / min, the first ball milling time is 110 min, the second ball milling speed is 1100 r / min, and the second ball milling time is 50 min.
[0070] In step (1), the mass ratio of the mixture of titanium dioxide and pyrophyllite, zirconium oxide and potassium titanate is 4:6.
[0071] In step (1), alumina grinding beads are used as grinding media in both the first ball milling and the second ball milling, and the medium ratio is 1:10.
[0072] In step (1), the drying temperature is 103° C. and the drying time is 4.5 h.
[0073] In step (2), the mass ratio of the composite filler to water is 1:30.
[0074] The mass of the polysiloxane in step (2) accounts for 0.2% of the mass of the composite filler.
[0075] In step (2), the rotation speed of high-speed stirring is 800 r / min, the time of high-speed stirring is 55 min, the reaction temperature is 70° C., and the reaction time is 4.8 h.
[0076] In step (2), anhydrous ethanol is used for washing three times, the drying temperature is 103° C., and the drying time is 5 h.
[0077] The manufacturers of the bleached eucalyptus kraft pulp and the bleached spruce kraft pulp in step (3) are both Guangxi Guangye Guitang Sugar Industry Group Co., Ltd.
[0078] In step (3), the mass ratio of bleached eucalyptus kraft pulp to bleached spruce kraft pulp is 4:6.
[0079] In step (3), the beating degree of the bleached eucalyptus sulfate pulp is 35°SR, and the mass concentration of the bleached eucalyptus sulfate pulp slurry is 5.5%; the beating degree of the bleached spruce sulfate pulp is 33°SR, and the mass concentration of the bleached spruce sulfate pulp slurry is 4.0%.
[0080] In step (4), the mass of the modified composite filler accounts for 16.5% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp, the mass of the dialdehyde starch accounts for 1.1% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp, the mass of the polyethyleneimine accounts for 0.9% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp, and the mass of the sodium tripolyphosphate accounts for 0.5% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp.
[0081] In step (4), the stirring speed is 1200 r / min and the stirring time is 40 min.
[0082] The decorative base paper prepared in Example 2 was tested for its performance, wherein the dry tensile strength was 5.52 kN / m, the whiteness was 94.06%, and the opacity was 98.18%.
[0083] Example 3
[0084] The method for preparing the decorative base paper described in Example 3 comprises the following steps:
[0085] (1) Pyrophyllite, zirconium oxide, potassium titanate, sodium hexametaphosphate and deionized water are uniformly mixed and ball-milled once to prepare a suspension, titanium dioxide is added to the suspension and ball-milled twice, and then filtered and dried to prepare a composite filler;
[0086] (2) dissolving the composite filler prepared in step (1) in water, then adding acetic acid to adjust the pH value of the system to 4, adding polysiloxane after high-speed stirring to react, filtering, washing, and drying after the reaction is completed to prepare a modified composite filler;
[0087] (3) pulping and beating bleached eucalyptus sulfate pulp and bleached spruce sulfate pulp to obtain bleached eucalyptus sulfate pulp slurry and bleached spruce sulfate pulp slurry, respectively, and then mixing the bleached eucalyptus sulfate pulp slurry and the bleached spruce sulfate pulp slurry to prepare a mixed slurry;
[0088] (4) Adding the modified composite filler, dialdehyde starch, polyethyleneimine and sodium tripolyphosphate prepared in step (2) to the mixed slurry prepared in step (3), stirring to make the mixture uniformly mixed to prepare a slurry, and then sequentially subjecting the obtained slurry to screen papermaking, wet paper sheet forming, and pressing and drying to prepare a decorative base paper.
[0089] in:
[0090] In step (1), the mass ratio of pyrophyllite, zirconium oxide and potassium titanate is 1:0.2:0.7.
[0091] In step (1), the mass ratio of the mixture of pyrophyllite, zirconium oxide and potassium titanate to sodium hexametaphosphate is 1:0.002.
[0092] In step (1), the mass ratio of the mixture of pyrophyllite, zirconium oxide and potassium titanate to deionized water is 1:1.7.
[0093] In step (1), the first ball milling speed is 1000 r / min, the first ball milling time is 115 min, the second ball milling speed is 1100 r / min, and the second ball milling time is 45 min.
[0094] In step (1), the mass ratio of the mixture of titanium dioxide and pyrophyllite, zirconium oxide and potassium titanate is 3:7.
[0095] In step (1), alumina grinding beads are used as grinding media in both the first ball milling and the second ball milling, and the medium ratio is 1:10.
[0096] In step (1), the drying temperature is 105°C and the drying time is 4 hours.
[0097] In step (2), the mass ratio of the composite filler to water is 1:30.
[0098] The mass of the polysiloxane in step (2) accounts for 0.3% of the mass of the composite filler.
[0099] In step (2), the rotation speed of high-speed stirring is 800 r / min, the time of high-speed stirring is 60 min, the reaction temperature is 68° C., and the reaction time is 4.8 h.
[0100] In step (2), anhydrous ethanol is used for washing 4 times, the drying temperature is 105° C., and the drying time is 5 h.
[0101] The manufacturers of the bleached eucalyptus kraft pulp and the bleached spruce kraft pulp in step (3) are both Guangxi Guangye Guitang Sugar Industry Group Co., Ltd.
[0102] In step (3), the mass ratio of bleached eucalyptus kraft pulp to bleached spruce kraft pulp is 4:6.
[0103] In step (3), the beating degree of the bleached eucalyptus sulfate pulp is 35°SR, and the mass concentration of the bleached eucalyptus sulfate pulp slurry is 5.5%; the beating degree of the bleached spruce sulfate pulp is 33°SR, and the mass concentration of the bleached spruce sulfate pulp slurry is 4.0%.
[0104] In step (4), the mass of the modified composite filler accounts for 17.5% of the total mass of the bleached eucalyptus sulfate pulp and the bleached spruce sulfate pulp, the mass of the dialdehyde starch accounts for 1.3% of the total mass of the bleached eucalyptus sulfate pulp and the bleached spruce sulfate pulp, the mass of the polyethyleneimine accounts for 0.7% of the total mass of the bleached eucalyptus sulfate pulp and the bleached spruce sulfate pulp, and the mass of the sodium tripolyphosphate accounts for 0.5% of the total mass of the bleached eucalyptus sulfate pulp and the bleached spruce sulfate pulp.
[0105] In step (4), the stirring speed is 1200 r / min and the stirring time is 45 min.
[0106] The decorative base paper prepared in Example 3 was tested for its performance, wherein the dry tensile strength was 5.58 kN / m, the whiteness was 94.15%, and the opacity was 98.31%.
[0107] Comparative Example 1
[0108] The preparation method of the decorative base paper described in Comparative Example 1 is the same as that of Example 1, except that zirconium oxide is not added in step (1). The decorative base paper prepared in Comparative Example 1 was tested for performance, wherein the dry tensile strength was 4.65 kN / m, the whiteness was 92.38%, and the opacity was 96.54%.
[0109] Comparative Example 2
[0110] The preparation method of the decorative base paper described in Comparative Example 2 is the same as that of Example 1, except that potassium titanate is not added in step (1). The decorative base paper prepared in Comparative Example 2 was tested for performance, wherein the dry tensile strength was 4.43 kN / m, the whiteness was 91.46%, and the opacity was 95.82%.
Claims
1. A method for preparing a decorative base paper, characterized in that: It consists of the following steps: (1) Pyrophyllite, zirconium oxide, potassium titanate, sodium hexametaphosphate and deionized water are uniformly mixed and ball-milled to prepare a suspension, titanium dioxide is added to the suspension and ball-milled for a second time, and then filtered and dried to prepare a composite filler; (2) dissolving the composite filler prepared in step (1) in water, then adding acetic acid to adjust the pH value of the system to 4, adding polysiloxane after high-speed stirring to react, filtering, washing, and drying after the reaction is completed to prepare a modified composite filler; (3) pulping and beating bleached eucalyptus sulfate pulp and bleached spruce sulfate pulp to obtain bleached eucalyptus sulfate pulp slurry and bleached spruce sulfate pulp slurry, respectively, and then mixing the bleached eucalyptus sulfate pulp slurry and the bleached spruce sulfate pulp slurry to prepare a mixed slurry; (4) Adding the modified composite filler, dialdehyde starch, polyethyleneimine and sodium tripolyphosphate prepared in step (2) to the mixed slurry prepared in step (3), stirring to make the mixture uniformly mixed to prepare a slurry, and then sequentially subjecting the obtained slurry to screen papermaking, wet paper sheet forming, and pressing and drying to prepare a decorative base paper.
2. The method for preparing the decorative base paper according to claim 1, characterized in that: In step (1), the mass ratio of pyrophyllite, zirconium oxide and potassium titanate is 1:0.2-0.3:0.5-0.7; In step (1), the mass ratio of the mixture of pyrophyllite, zirconium oxide and potassium titanate to sodium hexametaphosphate is 1:0.002; In step (1), the mass ratio of the mixture of pyrophyllite, zirconium oxide and potassium titanate to deionized water is 1:1.
7.
3. The method for preparing the decorative base paper according to claim 1, characterized in that: In step (1), the first ball milling speed is 1000 r / min, the first ball milling time is 110-115 min, the second ball milling speed is 1100 r / min, and the second ball milling time is 45-50 min; In step (1), the mass ratio of the mixture of titanium dioxide and pyrophyllite, zirconium oxide and potassium titanate is 3-4:6-7; In step (1), alumina grinding beads are used as grinding media in both the first ball milling and the second ball milling, and the medium ratio is 1:10; In step (1), the drying temperature is 103-105° C. and the drying time is 4-4.5 h.
4. The method for preparing the decorative base paper according to claim 1, characterized in that: In step (2), the mass ratio of the composite filler to water is 1:
30.
5. The method for preparing decorative base paper according to claim 1, characterized in that: In step (2), the mass of the polysiloxane accounts for 0.2%-0.3% of the mass of the composite filler.
6. The method for preparing decorative base paper according to claim 1, characterized in that: In step (2), the high-speed stirring speed is 800 r / min, the high-speed stirring time is 55-60 min, the reaction temperature is 68-70° C., and the reaction time is 4.8 h; In step (2), anhydrous ethanol is used for washing 3-4 times, the drying temperature is 103-105° C., and the drying time is 5 hours.
7. The method for preparing decorative base paper according to claim 1, characterized in that: In step (3), the mass ratio of bleached eucalyptus kraft pulp to bleached spruce kraft pulp is 4:
6.
8. The method for preparing decorative base paper according to claim 1, characterized in that: In step (3), the beating degree of the bleached eucalyptus sulfate pulp is 35°SR, and the mass concentration of the bleached eucalyptus sulfate pulp slurry is 5.5%; the beating degree of the bleached spruce sulfate pulp is 33°SR, and the mass concentration of the bleached spruce sulfate pulp slurry is 4.0%.
9. The method for preparing decorative base paper according to claim 1, characterized in that: In step (4), the mass of the modified composite filler accounts for 16.5-17.5% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp, the mass of the dialdehyde starch accounts for 1.1-1.3% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp, the mass of the polyethyleneimine accounts for 0.7-0.9% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp, and the mass of the sodium tripolyphosphate accounts for 0.5% of the total mass of the bleached kraft eucalyptus pulp and the bleached kraft spruce pulp.
10. The method for preparing decorative base paper according to claim 1, characterized in that: In step (4), the stirring speed is 1200 r / min and the stirring time is 40-45 min.
Citation Information
Patent Citations
Composite titanium dioxide and preparation method thereof
CN107254195A
Special ecological board decoration base paper and preparation method thereof
CN108330720A